Education and Consumer Informatics - Boyer, C.; Section Editor for the IMIA Yearbook Section on Education and Consumer Informatics (Yearbook of Medical Informatics, 2009)
Objectives This article presents the 2009 selection of the best papers presenting the advancements in the field of Education and Consumer Informatics with emphasis on quality online health information and its uses in the medical field.Method Synopsis of the articles selected for the IMIA yearbook 2009.Results Six papers from international peer reviewed journals where selected for this section.Conclusion The selection of articles gives an overview of the currently growing need for quality online health information and demonstrates the integration of online health information in medical care as well as the importance of continuing education through online training programs.
Keywords: Quality online information; criteria; training; education; online information